A community for students.

Here's the question you clicked on:

55 members online
  • 0 replying
  • 0 viewing

anonymous

  • 5 years ago

solve {2x-3y=11 7x-4y=6

  • This Question is Closed
  1. anonymous
    • 5 years ago
    Best Response
    You've already chosen the best response.
    Medals 0

    7*(2x-3y=11)= 11 2*(7x-4y=6)=6 multiplying both sides 13y=65 so y=5 so calculate x

  2. anonymous
    • 5 years ago
    Best Response
    You've already chosen the best response.
    Medals 0

    sry.. copy and paste made sm typo... but answer will be same 7*(2x-3y=11) 2*(7x-4y=6) multiplying both sides 13y=65 so y=5 so calculate x

  3. anonymous
    • 5 years ago
    Best Response
    You've already chosen the best response.
    Medals 0

    it will cm to 14x - 21y= 77 14x-18y=12 - + - (reversing the signs) -------------------------------- 13y=65 y=5

  4. anonymous
    • 5 years ago
    Best Response
    You've already chosen the best response.
    Medals 0

    is that matches ur answer Ashley?

  5. anonymous
    • 5 years ago
    Best Response
    You've already chosen the best response.
    Medals 0

    I appreciate ur help but i need to come out with an ordered pair for a graph. my answer sheet says the answer is (-2, -5)

  6. anonymous
    • 5 years ago
    Best Response
    You've already chosen the best response.
    Medals 0

    umm I think amit7808 made an error... I get your result lemme write the way I calculated it down:

  7. anonymous
    • 5 years ago
    Best Response
    You've already chosen the best response.
    Medals 0

    2x-3y=11 multiply by 4 since it is 4y in the equation below and we want to eliminate y 7x-4y=6 multiply by 3 since it is 3y in equation above so we can subtract both to obtain a solution for x => 8x-12y=44 21x+12y=18 :now we subtract the bottom one from the top and have a new bottom equation => 8x-12y=44 :top remains the same -13x =26 :bottom after subtracting, now we divide both sides by -13 so that we are left with 1x since -13/-13=1 and 1x=x on the left giving us the solution to x => x=26/-13= -2 we now insert -2 for x into the top equation to obtain y => 8*(-2)-12y=44 (one could also take the original version: 2*(-2)-3y=11) <=> -16-12y=44 now add 16 to both sides -12y=60 now same as before divide by minus twelve on both sides so we get 1*y=y => y=60/-12=-5 hope it is clear enough

  8. anonymous
    • 5 years ago
    Best Response
    You've already chosen the best response.
    Medals 0

    ya it will be -13y=65 so, y=-5 and x=-2 sry..

  9. Not the answer you are looking for?
    Search for more explanations.

    • Attachments:

Ask your own question

Sign Up
Find more explanations on OpenStudy
Privacy Policy

Your question is ready. Sign up for free to start getting answers.

spraguer (Moderator)
5 → View Detailed Profile

is replying to Can someone tell me what button the professor is hitting...

23

  • Teamwork 19 Teammate
  • Problem Solving 19 Hero
  • You have blocked this person.
  • ✔ You're a fan Checking fan status...

Thanks for being so helpful in mathematics. If you are getting quality help, make sure you spread the word about OpenStudy.

This is the testimonial you wrote.
You haven't written a testimonial for Owlfred.